2003
DOI: 10.1063/1.1566088
|View full text |Cite
|
Sign up to set email alerts
|

Effects of magnetic layer thickness and of head-to-medium spacing on noise in advanced particulate recording media

Abstract: Effects of magnetic layer thickness on noise in advanced double-layer metal particle tape Recording performance of the combination of magnetoresistive head and thin metal evaporated tapeThe effects of magnetic layer thickness on the noise characteristics of advanced metal particle tape have been observed using a dc demagnetization process generated with a uniform in-plane magnetizer. The three-dimensional ͑3D͒ surface maps of spectral noise power plotted as a function of remanent magnetization state showed a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…2, a trend can be seen at the lower frequencies where an overall increase in noise is observed with decreasing media thickness. Previous experimental [2] and modeling [4] studies have shown that large associations (e.g. clusters of magnetic particles formed in the wet stages of the manufacturing process) result in noise maxima in both of the magnetically saturated states.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2, a trend can be seen at the lower frequencies where an overall increase in noise is observed with decreasing media thickness. Previous experimental [2] and modeling [4] studies have shown that large associations (e.g. clusters of magnetic particles formed in the wet stages of the manufacturing process) result in noise maxima in both of the magnetically saturated states.…”
Section: Resultsmentioning
confidence: 99%
“…The rise in data densities has been accompanied by a necessary decrease in size of both the particles and thickness of the magnetic layer alongside an increase in read-head sensitivity such that media noise has become the limiting factor to further density increases. Previous studies have shown that the DC noise characteristics from the surface, bulk and lower interface of the magnetic layer are different and that in thick tapes (> 300 nm) the bulk dominates, whereas in thin tapes (~ 150 nm), the top surface is dominant [2]. In this paper we report an investigation of five very thin tapes (140 -50 nm) showing the effect of structure on noise as the magnetic/non-magnetic interface moves ever closer to the head in these advanced tape formats.…”
Section: Introductionmentioning
confidence: 99%